Determination and clinical features of bone pseudoprogression in metastatic breast cancer - Xu, Ting; Ma, Yikun; Zhang, Lili; Li, Shiyi; Dong, Min; Yuan, Yuan (Frontiers in Oncology, 2025)
ObjectiveBone is one of the most common sites of metastasis for breast cancer. The classification of new osteoblastic lesions as progressive disease is currently controversial. Computed tomography (CT), specifically the bone window setting, is the most frequently utilized for evaluating treatment efficacy in bone metastatic breast cancer (MBC). In this study, we aimed to assess the clinical features and significance associated with bone pseudoprogression.MethodsThis retrospective analysis was conducted among twenty-three MBC patients with new osteoblastic lesions during the first-line systemic therapy in Jiangsu Cancer Hospital from January 2018 to December 2023. After assessing treatment response every two cycles by CT (bone window) at least twice, we identified no disease progression in participants, thus defining new osteoblastic lesions as bone pseudoprogression. Participants continued treatment until explicit disease progression was observed (extraosseous disease progression or progressive lysis on bone lesions). Pretreatment baseline and follow-up alkaline phosphatase (ALP) levels were analyzed separately at the times of bone progression and pseudoprogression in the same patient.ResultsThe spine (78.2%) was the predominant metastatic site. The median time to the appearance of bone pseudoprogression after treatment was 1.73 months (95% CI: 1.42-2.04). Furthermore, the median interval between bone pseudoprogression and disease progression was 14.27 months (95% CI: 12.18-16.35). No significant difference in the interval was observed between HER2-positive and HER2-negative MBC patients (15.83 months versus 14.23 months, p=0.79). Compared to the occurrence of disease progression, the levels of ALP decreased or stabilized at pseudoprogression in the same patient. The difference in ΔALP between pseudoprogression and progression was statistically significant (-20U/L vs. 33 U/L, p< 0.001).ConclusionsOsteoblastic new lesions detected using CT (bone window) may be considered bone pseudoprogression, which predominantly occurs in the early stages of treatment. ALP serves as a biomarker for differentiating pseudoprogression from disease progression on CT (bone window) in patients with bone metastasis. Clinicians should exercise caution regarding the appearance of new osteoblastic lesions in patients not exhibiting extraosseous disease progression or progressive lysis on bone lesions.